Analisis Regresi Spasial Indeks Pembangunan Kesehatan Masyarakat dan Paradoks Simpson Kabupaten/Kota di Pulau Sumatera Tahun 2018 - Ujang Kurnia Krismayanto; Ernawati Pasaribu (Seminar Nasional Official Statistics, 2022)
Health is an important aspect of human development. Life Expectancy is used as a health indicator in the Human Development Index (HDI). The Ministry of Health Republic of Indonesia compiles the Community Health Development Index. This index is a more detailed indicator that describes public health. The Community Health Development Index value on the Sumatera island is very diverse, different from other islands in Indonesia. This study aims to obtain an overview of the variables studied, identify spatial effects, analyze the factors that influence the IPKM globally and locally, and identify the Simpson's Paradox phenomenon by comparing the results of the Multiple Linear Regression (MLR) and Geographically Weighted Regression (GWR) methods. This research consists of 154 regencies/cities in 10 provinces of Sumatra Island. The results showed that there was spatial heterogeneity, Life Expectancy was influential in 62,99% of regencies/cities on the Sumatra island. Average Length of School, Expenditure per Capita and Total Population each have an effect of 80,52%; 49,35%; 35,71% regencies/cities. There are differences in the direction of influence in several regions on several variables between the MLR and GWR methods. This shows the occurrence of the Simpson Paradox phenomenon. Based on the factors that influence the IPKM, it shows that there is a grouping based on the variables that influence it.